If god meant to interfere: American literature and the rise of the Christian right - Douglas, Christopher (Cornell University Press, 2016)
"Proposes to solve the question of how contemporary American literature has registered--or has failed to register--what is one of the most important cultural paradigm shifts of the postwar period, the astonishing expansion and empowerment of fundamentalist and conservative evangelical and Christianity in the United States"--